2021
DOI: 10.1155/2021/5555436
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Freeze‐Thaw Resistance of Stabilized Saline Soil

Abstract: In this paper, three freezing-thawing tests are designed to study the freeze-thaw resistance of stabilized sulfate type saline soil. The results show that different destructive modes and erosion extents are caused by different freeze-thaw conditions. The destructive effect from salt tends to be limited if there is no external water intrusion. When sufficient water is provided, ice expansion, dissolution recrystallization of salts, and ettringite growth during the thawing phase may take place. Soil water potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…It can be inferred that as the sample naturally dried, the Ca(OH) 2 formed by lime hydrolysis in the soil sample underwent a transformation from a colloidal to a crystalline state during the process of dry hardening. At the same time, Ca(OH) 2 carbonized with CO 2 in the air to form CaCO 3 [47], and the formation process was as follows Equations ( 9) and (10). As the sample is naturally A-D, the water glass is carbonized with CO 2 in the air to form a silicate gel.…”
Section: Microstructure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It can be inferred that as the sample naturally dried, the Ca(OH) 2 formed by lime hydrolysis in the soil sample underwent a transformation from a colloidal to a crystalline state during the process of dry hardening. At the same time, Ca(OH) 2 carbonized with CO 2 in the air to form CaCO 3 [47], and the formation process was as follows Equations ( 9) and (10). As the sample is naturally A-D, the water glass is carbonized with CO 2 in the air to form a silicate gel.…”
Section: Microstructure Analysismentioning
confidence: 99%
“…Zhu et al [9] proposed a new water-based polymer that can improve the strength, water stability, and dry-wet cycle resistance of saline soil. After studying the freeze-thaw (FT) resistance of stable sulfate saline soil, Zhou et al [10] proposed that a high proportion of stabilizers can improve the FT resistance of stable soil. Zhang et al [11] employed polypropylene fiber to reinforce red clay and investigate its strength and failure characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This could cause the volume to increase by more than 200%, resulting in salt heaving in the soil. In terms of chlorine saline soil, many researchers [23][24][25][26] measured the strength of the treated and untreated saline soil under short-term freeze-thaw cycles, and found that the treated saline soil gradually decreased, but the strength of untreated saline soil first increased and then decreased.…”
mentioning
confidence: 99%